(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study aimed to find out whether or not there was any significant difference in speaking ability of the students who were taught by implementing CML (Cultural Model for Literacy) through legends and those who were not. The sample was 41 undergraduate students enrolled in English course at FKIP of Sriwijaya University which were taken by purposive sampling method from 85 total of population. This study used one of the quasi-experimental designs that were pretest posttest non equivalent control group or comparison group design. The students were divided into two groups the experimental and control groups. The experimental group was required to do some phases in treatment of 16 meetings including pre-test and posttest in accordance with introducing new model of teaching speaking that was CML through legends. The data were obtained through speaking test by measuring their oral interpretations to know the students speaking ability. The test was administered twice as pre-test and post-test in both groups. The results indicated that there were any significant differences at level 0.05 level found in the data which were analyzed by using paired sample t-test (t=12.156>t-table=2.080) and independent sample t-test (t=3.252, p<0.05). The results also showed that CML through legends could enhance students speaking ability of the second semester English students of Sriwijaya University.